2023
DOI: 10.3390/ijms24021290
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Side Chain Oxidized Sterols as Novel Liver X Receptor Agonists with Therapeutic Potential in the Treatment of Cardiovascular and Neurodegenerative Diseases

Abstract: The nuclear receptors—liver X receptors (LXR α and β) are potential therapeutic targets in cardiovascular and neurodegenerative diseases because of their key role in the regulation of lipid homeostasis and inflammatory processes. Specific oxy(phyto)sterols differentially modulate the transcriptional activity of LXRs providing opportunities to develop compounds with improved therapeutic characteristics. We isolated oxyphytosterols from Sargassum fusiforme and synthesized sidechain oxidized sterol derivatives. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…Lipid extracts of the seaweed Sargassum fusiforme (S. fusiforme), which contain LXR-activating (oxy)phytosterols such as saringosterol, have been found to activate LXRs and prevent cognitive decline in AD mice [24]. Recently, we also identified (3β,22E)-3-hydroxycholesta-5,22-dien-24-one and fucosterol-24,28 epoxide as LXR agonists in S. fusiforme [25]. Unlike synthetic LXR agonists, these S. fusiforme extracts did not have adverse effects on hepatic or serum lipid levels, making them a promising alternative for clinical use [24,26].…”
Section: Introductionmentioning
confidence: 99%
“…Lipid extracts of the seaweed Sargassum fusiforme (S. fusiforme), which contain LXR-activating (oxy)phytosterols such as saringosterol, have been found to activate LXRs and prevent cognitive decline in AD mice [24]. Recently, we also identified (3β,22E)-3-hydroxycholesta-5,22-dien-24-one and fucosterol-24,28 epoxide as LXR agonists in S. fusiforme [25]. Unlike synthetic LXR agonists, these S. fusiforme extracts did not have adverse effects on hepatic or serum lipid levels, making them a promising alternative for clinical use [24,26].…”
Section: Introductionmentioning
confidence: 99%
“…For an active state, SREBP1c has to be cleaved from its 130 kDa precursor form located in the ER membrane to an active 60 kDa protein that can translocate into the nucleus. 38 Unlike synthetic LXR agonists, sterol-like LXR ligands appear to be weaker activators of the SREBP1c transcription, particularly in liver cells, 24 , 26 , 27 , 29 , 32 although some ligands can also selectively upregulate SREBP1c expression 39 or function as context-specific antagonists. 40 Furthermore, sterols and oxysterols were shown to inhibit the proteolytic activation of SREBP1c by binding to the SREBP cleavage-activating protein (SCAP) and insulin-induced gene 2 protein (INSIG2), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Limonoids isolated from T. prieuriana , especially those with a ring-intact structure ( 1 – 3 , Chart ), share a four-ring core structure similar to sterol-like LXR ligands. Among those with reported agonistic activity are desmosterol, , a precursor in the cholesterol synthesis pathway, endogenous and synthetic oxysterols, and other sterol derivatives, ,, as well as natural products of the triterpene type. This prompted us to investigate whether some limonoids are LXR agonists as well.…”
mentioning
confidence: 99%
“…It has been demonstrated that treatment with agonists for LXR and RXR leads to an increase in the levels of ABCA1 and APOE, as well as a reduction in amyloid deposition in the brains of mice overexpressing the APP [ 67 , 68 ]. Notably, 24-OHC, serving as a natural endogenous agonist of LXRs, has been shown to induce the up-regulation of ABCA1, ABCG1, and APOE expression [ 69 , 70 ]. Given the findings from the present study, which demonstrated an elevation in the brain levels of 24-OHC following exercise in APP/PS1 mice, we subsequently investigated alterations in nuclear transcription factors associated with cholesterol transport within the brain of APP/PS1 mice.…”
Section: Discussionmentioning
confidence: 99%